Analisis Pengaruh Objek Wisata, Jumlah Wisatawan, dan Tingkat Hunian Hotel terhadap Pertumbuhan Ekonomi di Kabupaten Malang - Tarwiyah Ayu Permatasari; Marseto Marseto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Economic growth is a macroeconomic indicator of concern because it reflects a country's ability to increase the per capita income of its population. Economic growth is supported by economic sectors that have potential, one of which is tourism which can have a good impact on regional development such as improving the regional economy, increasing creativity and innovation and improving the welfare of the community. This study was conducted to analyze the influence of tourist attractions, the number of tourists, and hotel occupancy rates on economic growth in Malang Regency. The method used in this study is the Ordinary Least Square (OLS) Multiple Linear Regression analysis method with time series data using SPSS Version 26 software. The data used in this study are the number of tourist attractions, the number of tourist visits, and hotel occupancy rates as independent variables and economic growth as a dependent variable within a period of 15 years, namely in 2008-2022. The results obtained from this study state that simultaneously tourist attractions, the number of tourists, and hotel occupancy rates have a significant effect on economic growth. However, partially each variable has no effect on economic growth. Keywords:Tourism, Tourist Attractions, Tourists, Hotel Occupancy, and Economic Growth.